1997
DOI: 10.1001/archinte.1997.00440300089007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Clinicians' Performance for Detecting Actinic Keratoses and Skin Cancer

Abstract: Examinations performed by primary care clinicians for diagnosing skin cancer lacked sensitivity. Without improved diagnostic skills, primary care clinicians' examinations may be ineffective as a screening test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…6,14,18,35,36 Our finding that primary care physicians were less likely to counsel their patients on skin cancer and sunscreen use if those physicians were from an academic or hospital setting is consistent with a recent survey that found pediatricians in health maintenance organizations and private settings more likely to counsel about skin cancer than pediatricians in academic institutions or community health centers. 15 Perhaps office and managed care settings are more likely to have guidelines addressing skin cancer prevention.…”
Section: Arch Dermatol / Vol 136 May 2000supporting
confidence: 85%
“…6,14,18,35,36 Our finding that primary care physicians were less likely to counsel their patients on skin cancer and sunscreen use if those physicians were from an academic or hospital setting is consistent with a recent survey that found pediatricians in health maintenance organizations and private settings more likely to counsel about skin cancer than pediatricians in academic institutions or community health centers. 15 Perhaps office and managed care settings are more likely to have guidelines addressing skin cancer prevention.…”
Section: Arch Dermatol / Vol 136 May 2000supporting
confidence: 85%
“…It is reassuring for us, but perhaps not for patients, that our results are echoed in studies from other countries. Whited et al (1997) showed that primary care clinicians identified the presence of skin cancer with a sensitivity of 57% (95% CI, 44 -68%) in one US study and ). In the face of rising skin cancer incidence it is clear that the major challenge of providing minor surgery in primary care is the potential for missed diagnosis of serious skin malignancies (Diffey, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Whited et al 10 examined the ability of primary care physicians to diagnose AKs and NMSC using der- matologists' clinical impressions as the gold standard and found again that for the diagnosis of AKs, the interobserver variability among dermatologists was unreliable.…”
Section: Commentmentioning
confidence: 99%